How do people with dementia use the ambulance service? A retrospective study in England: the HOMEWARD project. Issue 7 (1st August 2018) - Voss, Sarah; Brandling, Janet; Taylor, Hazel; Black, Sarah; Buswell, Marina; Cheston, Richard; Cullum, Sarah; Foster, Theresa; Kirby, Kim; Prothero, Larissa; Purdy, Sarah; Solway, Chris; et al.
Abstract : Objectives: An increasing number of older people are calling ambulances and presenting to accident and emergency departments. The presence of comorbidities and dementia can make managing these patients more challenging and hospital admission more likely, resulting in poorer outcomes for patients. However, we do not know how many of these patients are conveyed to hospital by ambulance. This study aims to determine: how often ambulances are called to older people; how often comorbidities including dementia are recorded; the reason for the call; provisional diagnosis; the amount of time ambulance clinicians spend on scene; the frequency with which these patients are transported to hospital. Methods: We conducted a retrospective cross-sectional study of ambulance patient care records (PCRs) from calls to patients aged 65 years and over. Data were collected from two ambulance services in England during 24 or 48 hours periods in January 2017 and July 2017. The records were examined by two researchers using a standard template and the data were extracted from 3037 PCRs using a coding structure. Results: Results were reported as percentages and means with 95% CIs. Dementia was recorded in 421 (13.9%) of PCRs. Patients with dementia were significantly less likely to be conveyed to hospital following an emergency call than those without dementia. The call cycle times were similar for patients regardless of whether or not they had dementia. Calls to people with dementia were more likely to be due to injury following a fall. In the overall sample, one or more comorbidities were reported on the PCR in over 80% of cases. Conclusion: Rates of hospital conveyance for older people may be related to comorbidities, frailty and complex needs, rather than dementia. Further research is needed to understand the way in which ambulance clinicians make conveyance decisions at scene.